MARRIAGE AS A MORAL REHABILITATION EFFORT FOR PORNOGRAPHY ADDICTS: A REVIEW OF MAQĀṢID AL-SYARĪ‘AH - Fadlillah Alif Baihaqi; Yusdi Haq (Program Pascasarjana UIN Sumatera Utara, 2026)
The phenomenon of pornography in the digital era is no longer merely understood as an individual moral issue, but has evolved into a social problem that affects self-control, sexual behavior, and family stability. Studies of Islamic law have tended to focus on prohibition and prevention, while rehabilitative approaches to pornography addicts remain relatively limited. This study aims to analyze and construct arguments regarding the role of marriage as a mechanism for moral rehabilitation for pornography addicts from the perspective of maqāṣid al-syarī‘ah. The study uses a qualitative approach with library research analyzed through a thematic-conceptual approach based on maqāṣid al-syarī‘ah. Data sources include the Qur'an, hadith, maqāṣid literature, and scientific research related to pornography, sexual behavior, and Islamic family law. The results of the study indicate that pornography disrupts the protective functions of reason (ḥifẓ al-‘aql), honor (ḥifẓ al-‘ird), and offspring (ḥifẓ al-nasl).